The expert government of disaster in Africa: disaster science between states and international organisations - (:unkn) unknown (My University, 2013)
Panel African experts in the international government of Africa, mod. David Ambrosetti, Jean-Hervé Jézéquel et Marie-Emmanuelle Pommerolle http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2047
Keywords: African Research